2010
DOI: 10.20506/rst.29.3.2004
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of peste des petits ruminants in migratory flocks of sheepand goats in egypt in 2006

Abstract: An outbreak of peste des petits ruminants (PPR) was recorded in Kalubia province, Egypt in 2006, affecting a large population of migratory goats and sheep over a huge geographical area. Epidemiological, clinical and laboratory investigations were performed. Diseased animals showed pyrexia, erosive stomatitis, enteritis and bronchopneumonia. Clinical manifestations were more severe in goats. The overall morbidity, cumulative mortality and case fatality rates were 26.1%, 10.5% and 40.2%, respectively, and were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 16 publications
5
33
0
Order By: Relevance
“…The morbid pathomorphological lesions in lungs, trachea, caecum, spleen, liver, heart and kidneys observed in this study were partly in agreement with previous report made by El-Yuguda et al, (2009) Zahur et al, (2009), Abd El-Rahim et al, (2010, Chauhan et al, (2011), Jagtap et al, (2012), Rosemary et al, (2013), and Ekambaram et al, (2015) in sheep and goat. The pneumonic lungs and hemorrhagic trachea probably due to descending upper respiratory infection of PPR complicated by secondary bacterial infection (Rosemary et al, 2013).…”
Section: Resultssupporting
confidence: 93%
“…The morbid pathomorphological lesions in lungs, trachea, caecum, spleen, liver, heart and kidneys observed in this study were partly in agreement with previous report made by El-Yuguda et al, (2009) Zahur et al, (2009), Abd El-Rahim et al, (2010, Chauhan et al, (2011), Jagtap et al, (2012), Rosemary et al, (2013), and Ekambaram et al, (2015) in sheep and goat. The pneumonic lungs and hemorrhagic trachea probably due to descending upper respiratory infection of PPR complicated by secondary bacterial infection (Rosemary et al, 2013).…”
Section: Resultssupporting
confidence: 93%
“…57,59,62,65,66,67,68,70,72,74,79,80,81,84,86,87,88,89,90,93,94,95,97,98,99,105,106,109,112,113,114,116,117,118,119,120,121,125,126,128,130,131,132,133,135,137,138,139,141,142,145,147,…”
Section: Study Eligibility Form: Performance Of Diagnostic Tests For mentioning
confidence: 99%
“…were common disease problems occurred in Raika shepherds but highest mortality in sheep flocks occurred due to sheep pox and reduced flock strength by half or even more. In similar line Abd El- Rahim et al, (2010) reported significantly higher mortality of young animals in migratory flocks due to diseases problems in Egypt. Mortality rate was also observed more in young one in migratory sheep in Thar Desert of Rajasthan (Kataria et al, 2007), Tamil Nadu (Thiruvenkadan et al, 2007) and Andhra Pradesh (Rao et al, 2011).…”
Section: Mortality Ratementioning
confidence: 54%
“…Contrary to our results, higher incidence of enterotoxaemia (32%), FMD (34.9%), pox (42.6%) and PPR (63.5%) was observed by Garner et al, (2000). Abd El-Rahim et al, (2010) in Egypt also reported higher overall incidence of PPR (26.1%) in migratory flocks. The incidence of pox observed in the present study is in similar line with previous reports (Jindal et al, 2006;Suresh et al, 2008;Selvaraju and Balasubramaniam, 2013;, who reported that incidence of sheep pox ranged from 2.0 to 18.18% in different sheep flocks.…”
Section: Disease Incidencementioning
confidence: 77%
See 1 more Smart Citation